2022
DOI: 10.3390/microorganisms10061198
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Cyanobacteria to the Endolithic Light Spectrum in Hyper-Arid Deserts

Abstract: In hyper-arid deserts, endolithic microbial communities survive in the pore spaces and cracks of rocks, an environment that enhances water retention and filters UV radiation. The rock colonization zone is enriched in far-red light (FRL) and depleted in visible light. This poses a challenge to cyanobacteria, which are the primary producers of endolithic communities. Many species of cyanobacteria are capable of Far-Red-Light Photoacclimation (FaRLiP), a process in which FRL induces the synthesis of specialized c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…CCMEE 010 far-red cluster is distinct not only from the cluster in the related Chroococcidiopsis thermalis PCC 7203 but also from clusters in more distantly related strains such as the heterocyst-forming cyanobacteria ( Supplementary Figure 2 ). A Chroococcidiopsis -associated cluster recovered from an Atacama metagenome also did not show these changes ( Murray et al, 2022 ). Notably, psaF and psaJ were inserted between psbC and psbB , which has not been observed in any other FaRLiP clusters ( Gan et al, 2014 , 2015 ; Chen et al, 2019 ; Sheridan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…CCMEE 010 far-red cluster is distinct not only from the cluster in the related Chroococcidiopsis thermalis PCC 7203 but also from clusters in more distantly related strains such as the heterocyst-forming cyanobacteria ( Supplementary Figure 2 ). A Chroococcidiopsis -associated cluster recovered from an Atacama metagenome also did not show these changes ( Murray et al, 2022 ). Notably, psaF and psaJ were inserted between psbC and psbB , which has not been observed in any other FaRLiP clusters ( Gan et al, 2014 , 2015 ; Chen et al, 2019 ; Sheridan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such a low FaRLiP occurrence among desert strains of Chroococcidiopsis suggested that this photoacclimation mechanism might not be common among rock-inhabiting cyanobacteria. Enrichment cultures may nevertheless reveal it, for instance, in samples from Negev sandstone or the Atacama Desert ( Murray et al, 2022 ). It is possible that intense abiotic stress could result in reduced competition from other photosynthetic organisms ( Lacap-Bugler et al, 2017 ) and, consequently, a decreased evolutionary pressure to maintain a complex acclimation response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the ecological role of cyanobacteria with FaRLiP in natural habitats remains much less explored. Cyanobacteria with Chl f have been found in a variety of terrestrial (Behrendt et al, 2015(Behrendt et al, , 2010Zhang et al, 2019;Murray et al, 2022) and aquatic (e.g. Akutsu et al, 2011;Trampe and Kühl, 2016;Ohkubo and Miyashita, 2017) habitats.…”
Section: Introductionmentioning
confidence: 99%